Basic methods of structural geology - Marshak, Stephen (Prentice-Hall / New Jersey, 1988)
This versatile book in intended to be used both as a text for students and a reference manual professional. Because topic build gradually from elementary concepts to complex techniques, beginning students are not overwhelmed and advanced readers will find challenges